2019
DOI: 10.1038/s41598-019-49038-8
|View full text |Cite
|
Sign up to set email alerts
|

A20 deficiency in hematopoietic stem cells causes lymphopenia and myeloproliferation due to elevated Interferon-γ signals

Abstract: Inflammation and inflammatory cytokines have been shown to exert both positive and negative effects on hematopoietic stem cells (HSCs) and hematopoiesis. While the significance of inflammation driven hematopoiesis has begun to unfold, molecular players that regulate this phenomenon remain largely unknown. In the present study, we identified A20 as a critical regulator of inflammation controlled hematopoietic cell fate decisions of HSCs. A20 deficiency in HSCs leads to increased differentiation of myeloid cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
(66 reference statements)
2
5
0
Order By: Relevance
“…This hematopoietic phenotype very closely resembles phenotypes observed when a phosphorylationmimic Ikk2 (IKBKB) S177E, S181E was expressed panhematopoietically in mice, either heterozygously (129) or homozygously (130). It also resembles mouse phenotypes obtained when A20/TNFAIP3, an inhibitor of NFkB signaling activation by activated TNFR1, TLRs, and other signaling receptors, was eliminated (131)(132)(133)(134). Furthermore, the .…”
Section: Nfκb Pathway Hyperactivation Is Systemic In Mpns and May Affect Stromal-hematopoietic Interactionssupporting
confidence: 67%
See 1 more Smart Citation
“…This hematopoietic phenotype very closely resembles phenotypes observed when a phosphorylationmimic Ikk2 (IKBKB) S177E, S181E was expressed panhematopoietically in mice, either heterozygously (129) or homozygously (130). It also resembles mouse phenotypes obtained when A20/TNFAIP3, an inhibitor of NFkB signaling activation by activated TNFR1, TLRs, and other signaling receptors, was eliminated (131)(132)(133)(134). Furthermore, the .…”
Section: Nfκb Pathway Hyperactivation Is Systemic In Mpns and May Affect Stromal-hematopoietic Interactionssupporting
confidence: 67%
“…HSPC phenotypes were dependent on NFkB hyperactivation in HSPC, as they could be entirely rescued by hematopoietic expression of the nondegradable IkBa S32A, S36A "super repressor" mutant. NFkB hyperactivation in HSPC promoted myeloid differentiation with loss of HSPCs and lymphocytes, resulting in pancytopenia and bone marrow failure (a phenotype also observed to result from pan-hematopoietic NFkB hyperactivation in mice) (129)(130)(131)(132)(133). (B) Bone marrow remodeling by hematopoietic Jak2 V617F, analogous to human MPNs.…”
Section: Nfκb Pathway Hyperactivation Is Systemic In Mpns and May Affect Stromal-hematopoietic Interactionsmentioning
confidence: 99%
“…Highlighting the physiological role of A20, various polymorphisms of the A20/TNFAIP3 gene resulting in reduced expression of functional gene product are linked to inflammatory and autoimmune diseases (22,23). With respect to cancers, A20's role remains controversial, because A20 may be oncogenic or tumor suppressive depending on the tissue of origin (24)(25)(26)(27)(28)(29). In this work, we found a function for A20 in NSCLC.…”
Section: Introductionmentioning
confidence: 57%
“…Consistently, our studies demonstrated that loss of Itch (a member of HECT domain family of E3 ligases) caused abnormal hematopoiesis and defective HSC functions 57 . Recent studies from our lab established that a deficiency of A20 (a ubiquitin editing enzyme) causes severe HSC defects and functions, which ultimately leads to pancytopenia and premature death 37,58,59 . Interestingly, Trim28 protein possesses a RING finger domain and has been identified to exert E3 ubiquitin ligase functions on substrates including p53, AMPK and CDK9 proteins 13,60 .…”
Section: Discussionmentioning
confidence: 99%